Complexes of Si (IV), Ge (IV), Sn (IV), Ti (IV) and Zr (IV) Metals with N,N´ — Bis(8-Aceto-7-hydroxy-2-methyl coumarin)Hydrazine Schiff Base - P. Pokhariyal, Ganesh (Asian Journal of Chemistry, 2010)
N,N´-Bis (8-aceto-7-hydroxy-4-methyl coumarin) hydrazine (AHCHy) has been synthesised from 8-acetyl-7-hydroxy-4-methyl eoumarin (AHC) with hydrazine hydrate. Group IV metal complexes with (AHCHy) has been prepared and characterised on the basis of elemental analysis. IR spectroscopy, conductance measurements and molecular weight determination.